The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fimmu.2019.01054
|View full text |Cite
|
Sign up to set email alerts
|

Role of C5b-9 and RGC-32 in Cancer

Abstract: The complement system represents an effective arsenal of innate immunity as well as an interface between innate and adaptive immunity. Activation of the complement system culminates with the assembly of the C5b-9 terminal complement complex on cell membranes, inducing target cell lysis. Translation of this sequence of events into a malignant setting has traditionally afforded C5b-9 a strict antitumoral role, in synergy with antibody-dependent tumor cytolysis. However, in recent decades, a plethora of evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 94 publications
0
16
0
Order By: Relevance
“…Subsequent studies have shown that RGC-32 is an important cell cycle regulator, driving cell cycle progression in a number of cell types, such as smooth muscle cells and endothelial cells, by promoting the activity of CDC2/cyclin B complexes and Akt kinase (2,3). RGC-32 has also been shown to be involved in cell differentiation, tumorigenesis, and wound healing (4,5). Furthermore, RGC-32 has been found to be crucial for the TGFb-induced epithelial-to-mesenchymal transition in renal fibrosis and cancer metastasis (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies have shown that RGC-32 is an important cell cycle regulator, driving cell cycle progression in a number of cell types, such as smooth muscle cells and endothelial cells, by promoting the activity of CDC2/cyclin B complexes and Akt kinase (2,3). RGC-32 has also been shown to be involved in cell differentiation, tumorigenesis, and wound healing (4,5). Furthermore, RGC-32 has been found to be crucial for the TGFb-induced epithelial-to-mesenchymal transition in renal fibrosis and cancer metastasis (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…In chronic inflammation, anaphylatoxins—particularly C5a—can promote a protumor microenvironment through a variety of mechanisms, including chemotactic recruitment of tissue‐infiltrating myeloid cells that are stimulated to secrete immunosuppressive molecules, thereby sustaining a protumor microenvironment 58 . In addition, sublytic terminal complement complexes can have oncogenic effects, including cell cycle modulation and resistance to apoptosis and complement 59 . Mechanisms of tumor cell complement evasion include antigenic modulation 60 and overexpression of complement regulatory proteins, of which CD59 (membrane attack complex‐inhibitory protein, or protectin) inhibits C9 polymerization and can induce internalization of affected areas of membrane in order to escape membrane attack complex lysis 61 .…”
Section: Role In Tumor Promotion and Eliminationmentioning
confidence: 99%
“…Under the action of these proteins, the MAC cannot form a complete permeable pore across the cell membrane and becomes a partially dissolved form, sublytic C5b-9(sC5b-9), which is embedded in the membrane. sC5b-9 can activate multiple signaling pathways, including PI3K-Akt, ERK, JAK1-STAT3, and NF-ÎșB, and regulates tumor cell growth in a G protein-dependent manner ( Vlaicu et al, 2019 ). sC5b-9 is highly expressed in lymphomas and oral squamous cell carcinoma cells ( Niculescu et al, 1997 ; Pilzer and Fishelson, 2005 ; Gallenkamp et al, 2018 ).…”
Section: The Complement Systemmentioning
confidence: 99%
“…RGC32 is involved in cell differentiation, cell cycle regulation, and immune regulation under physiological conditions ( Badea et al, 1998 ; Vlaicu et al, 2008 ). In tumors, the expression and function of RGC32 are disease-dependent ( Vlaicu et al, 2019 ). RGC32 is highly expressed in colon cancer, breast cancer, ovarian cancer, gastric cancer, pancreatic cancer, esophageal cancer, prostate cancer, and lymphoma.…”
Section: The Complement Systemmentioning
confidence: 99%
See 1 more Smart Citation